THE EFFECTIVENESS OF MISOPROSTOL COMPARES TO OXYTOCIN IN MANAGEMENT OF RETAINED PLACENTA: AN EVIDENCE-BASED CASE REPORT - Gunawan, Indra; Damanik, Roni Andre Syahputra (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2021)
ABSTRACT Introduction: Retained placenta is one of major cause for postpartum haemorrhage. Various medication and routes of administration have been reported to increase spontaneous placenta delivery and prevent manual removal of placenta. Purpose of the study to compare the outcome between misoprostol and oxytocin in management of retained placenta. Method: literature searching was done in 4 databases (Pubmed, EbscoHost, Cochrane and Scopus) with specific keywords, continued with article selection and critical appraisal. Result: 5 randomized controlled trial articles were found match to eligibility criteria. 3 of 5 studies found that spontaneous placental delivery occurred more in misoprostol group than oxytocin group. Based on 2 studies, the NNT value of misoprostol are 3 compare to oxytocin group. 2 other studies found that no significant differences of spontaneous delivery of placenta in misoprostol and oxytocin group. 2 studies found that misoprostol had shorter time for spontaneous placenta delivery. However, 2 other studies also found that misoprostol had longer time for spontaneous delivery. 1 study also found that Misoprostol group have less blood loss than oxytocin group. Conclusion: administration of misoprostol has better outcome in induce spontaneous placenta delivery, time needed for delivery and less blood loss volume compared to oxytocin. Keywords: misoprostol; oxytocin; prolonged third stage labour; retained placenta